Nrf2 Suppression Delays Diabetic Wound Healing Through Sustained Oxidative Stress and Inflammation - Li, Min; Yu, Haibing; Pan, Haiyan; Zhou, Xueqing; Ruan, Qiongfang; Kong, Danli; Chu, Zhigang; Li, Huawen; Huang, Jingwen; Huang, Xiaodong; Chau, Angel; Xie, Weiguo; et al. (Frontiers in Pharmacology, 2019)
Impaired wound healing is one of the major complications of diabetes, involving prolonged inflammation, delayed reepithelialization and consistent oxidative stress. The detailed mechanism remains unclear, and there is currently no effective treatment for diabetic wound healing. In this study, we aim to investigate the potential role and effect of Nrf2 (nuclear factor erythroid-2-related factor-2) activation on diabetic wound healing. In vitro experiments in rat macrophages showed that hyperglycemia treatment suppresses Nrf2 activation, resulting in oxidative stress with decreased expression of antioxidant genes, including NQO1 (NAD(P)H:quinone oxidoreductase 1) and HO1 (heme oxygenase 1), together with increased secretion of pro-inflammatory cytokines, including IL1β, IL6 and MCP1 (monocyte chemoattractant protein-1). Both Nrf2 overexpression and Nrf2 activator dimethyl fumarate (DMF) treatment significantly ameliorated oxidative stress and inflammation. On the other hand, both Nrf2 knockdown or Nrf2 inhibitor ML385 mimicked the effect of diabetes. Further in vivo experiments in rats showed that DMF treatment significantly accelerated wound healing in streptozocin (STZ)-induced diabetic rats with increased expression of antioxidant enzymes and decreased secretion of pro-inflammatory cytokines, while Nrf2 inhibitor ML385 mimicked the effect of diabetes. We conclude that Nrf2 activation accelerates impaired wound healing by ameliorating diabetes-mediated oxidative stress and inflammation. This provides a new clinical treatment strategy for diabetic wound healing using Nrf2 activator DMF.